2007
DOI: 10.1016/j.foreco.2007.01.081
|View full text |Cite
|
Sign up to set email alerts
|

Biomass conversion factors (density and carbon concentration) by decay classes for dead wood of Pinus sylvestris, Picea abies and Betula spp. in boreal forests of Sweden

Abstract: For estimating the amount of carbon (C) in dead wood, conversion factors from raw volume per decay class to dry weight were developed using three different classification systems for the species Norway spruce (Picea abies L. Karst), Scots pine (Pinus sylvestris L.) and birch (Betula pendula Roth and B. pubescens Ehrh) in Sweden. Also the C concentration in dead wood (dry weight) was studied. About 2500 discs were collected from logs in managed forests located on 289 temporary National Forest Inventory (NFI) sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
52
2
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 27 publications
7
52
2
3
Order By: Relevance
“…In our study area, the CWD volume was ranging between 16 and 78 m 3 ha -1 , thus at the lower end of the above-mentioned range. The measured Cstocks in the CWD corresponded well to values reported in the literature for similar sites (Sandström et al 2007). CWD is a nonnegligible C reservoir in subalpine forests.…”
Section: Carbon Stocks In Cwdsupporting
confidence: 87%
“…In our study area, the CWD volume was ranging between 16 and 78 m 3 ha -1 , thus at the lower end of the above-mentioned range. The measured Cstocks in the CWD corresponded well to values reported in the literature for similar sites (Sandström et al 2007). CWD is a nonnegligible C reservoir in subalpine forests.…”
Section: Carbon Stocks In Cwdsupporting
confidence: 87%
“…In the case of coarse woody debris, dead standing trees, and snags, deadwood decomposition was taken into account by applying to the CS a reducing factor (based on Yatskov et al (2003) and Sandström et al (2007)) corresponding to the decomposition degree among the three classes observed on the field: 1, if no decomposition occurred; 0.75, if decomposition was in progress; and 0.5, when the wood was highly decomposed. The litter CS was calculated based on the litter carbon data of 120 RFIW plots.…”
Section: Living Biomass and Deadwoodmentioning
confidence: 99%
“…Per tali motivi, data anche la difficoltà di misura della necromassa di piccole e medie dimensioni in termini di volume (Sandström et al 2007) si è optato per la determinazione del peso secco del materiale legnoso.…”
Section: Rilievi In Campo E Analisi DI Laboratoriounclassified
“…Inoltre, considerato che le caratteristiche del materiale legno so al suolo sono condizionate dalle dinamiche che hanno portato alla morte della pianta o parte di essa (Gilg 2004, Christensen et al 2005, Mircu et al 2006 e che il quantitativo e la tipologia di CWD cambiano a seconda degli stadi successionali della foresta, è lo gico affermare che col crescere dell'età del bosco la quantità di legno aumenti così come anche le dimen sioni medie del materiale accumulato (Harmon et al 1986, Wolynski 2001. Diversi autori (Wolynski 2001, Christensen et al 2005, Ekbom et al 2006, Sandström et al 2007) affermano che la quantità di CWD è mi nore in boschi sottoposti a tagli colturali rispetto a quella presente in soprassuoli lasciati alla naturale evoluzione. Di Filippo et al (2004) sostengono che l'abbondanza di necromassa come conseguenza del l'assenza delle utilizzazioni forestali è uno degli ele menti più rappresentativi della vetustà di una fore sta.…”
Section: Figunclassified